Enhancement of Internal Business Process Using Artificial Intelligence - Santoso, Joseph Teguh; Wibowo, Agus; Raharjo, Budi (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2024)
This research aims to explore the feasibility of Artificial Intelligence (AI) enabled process improvement systems to assist businesses in optimizing Internal Business Process (IBP) by making and adopting suggestions and improvements. Over the last two decades’ technological advances in the new generation have allowed us to use more sophisticated systems to speed up different tasks, as well as AI which has cognate from theory to something more efficient and applicable. This study confirms that a feasible AI-based system can provide benefits to companies in terms of increasing revenue. A mixed method was used; quantitative research was carried out through surveys to gather knowledge about the use of AI in the IBP, while qualitative research was carried out through interviews to obtain an overview of the use of AI in certain IBP. The results show that constructing AI in process optimization is a complicated task than one might expect.